Nomenclature of Pancreatic Fluid Collections following Acute Pancreatitis: Need to Further Revise the Atlanta Classification System! - Rana, Surinder Singh; Gupta, Rajesh (Journal of Digestive Endoscopy, 2022)
A better understanding of the disease pathophysiology, improved imaging modalities, and the development of minimally invasive interventions led to the revision of the Atlanta classification and new terminologies for the pancreatic fluid collections (PFCs) occurring in acute pancreatitis. Peripancreatic necrosis (PPN) or extra-pancreatic necrosis (EPN) has been reported as a distinct morphological entity with a better outcome than combined pancreatic and peripancreatic necrosis as well as pancreatic parenchymal necrosis alone and slightly worse than acute interstitial pancreatitis. In this news and views, we discuss a study that compared the morphological features and outcomes of endoscopic drainage of walled off necrotic collections developing after EPN alone with those developing after PN with or without EPN.
Keywords: endosonography; necrosectomy; stent; walled-off necrosis